2006
DOI: 10.1021/la061108g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanometer-Scale Polymeric Structures on Surfaces from Template Assisted Admicellar Polymerization:  A Comparative Study with Protein Adsorption

Abstract: A novel method for the formation of nanometer-scale polymer structures via template assisted admicellar polymerization (TAAP) is described. Admicellar polymerization uses a surfactant layer adsorbed on a surface to localize monomer to the surface prior to polymerization of the monomer. Nanostructures are formed by restricting adsorption to the uncovered sites of an already-templated surface, in this case to the interstitial sites between adsorbed latex spheres. Unlike most other process that form polymer nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…This technique was used to coat various substrates with polymers like polystyrene (PS) and poly methyl methacrylate (PMMA) [42][43][44][45][46] . This coating technique was also applied to study the method of polymer coating formation on graphite and mica surfaces [47][48][49][50][51] . Chen et al had previously demonstrated that the micelle surrounding single-walled carbon nanotubes (SWNTs) could be swelled by various organic solvents 52 .…”
mentioning
confidence: 99%
“…This technique was used to coat various substrates with polymers like polystyrene (PS) and poly methyl methacrylate (PMMA) [42][43][44][45][46] . This coating technique was also applied to study the method of polymer coating formation on graphite and mica surfaces [47][48][49][50][51] . Chen et al had previously demonstrated that the micelle surrounding single-walled carbon nanotubes (SWNTs) could be swelled by various organic solvents 52 .…”
mentioning
confidence: 99%
“…Effects of topological variations were observed experimentally at much larger distances in the work of Marquez et al, who used nanosphere lithography on highly-ordered pyrolytic graphite and template assisted admicellar polymerization to create nanostructures with different sized polystyrene nanospheres, which caused confinement both laterally and vertically. [13] Continuous honeycomb structures formed when using spheres larger than 500 nm while smaller spheres yielded discontinuous spikes; in all cases the polymer film was not completely filling the interstitial void space. A simple geometric argument revealed that the polymer-sphere separation distance varied between 4 nm and 250 nm, depending on nanoparticle size.…”
Section: Introductionmentioning
confidence: 97%
“…An indirect observation of this phenomenon was provided by Marquez et al, 41 who adsorbed surfactants on a surface to seed the so-called "template assisted admicellar polymerization". 42 Admicellar polymerization refers to a process by which monomers segregate within surfactant self-assembled aggregates. The monomers are then polymerized to obtain the final permanent polymeric structures.…”
Section: ■ Introductionmentioning
confidence: 99%